Effects of bench press eccentric tempo modification on dynamic and static strength performance in powerlifting athletes with disabilities - Méndez-DelCanto, R.; Aidar, F.; Banja, T.; dos Santos, J.; da Silva-Grigoletto, M.; Marçal, A.; Aedo-Muñoz, E.; Brito, C.; Nikolaidis, P. (Sport Sciences for Health, 2025)
Background Paralympic powerlifting (PP) competition demands maximal concentric force exertion during the bench press. Since modifying the eccentric tempo can directly affect concentric outcomes, this study aimed to investigate the effects of different bench press eccentric tempos on dynamic and static strength performance in PP athletes.